2013
DOI: 10.1002/ejoc.201300357
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Star‐Shaped Donor–Acceptor–Donor Structures

Abstract: A Sonogashira coupling reaction led to star‐shaped 1,3,5‐tris({5‐[7‐(thiophen‐2‐yl)benzo[c][1,2,5]thiadiazol‐4‐yl]thiophen‐2‐yl}ethynyl)benzene derivatives. The star‐shaped molecules were optically analyzed, and – depending on their substitution pattern – they displayed bathochromically shifted absorptions, which were compared to their nonlinked arm precursors. The materials displayed a highly interesting morphology in bulk when blended with [6,6]‐phenyl‐C61‐butyric acid methyl ester (PCBM). One derivative for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…When BT is incorporated with electron donor units, the extension of the conjugated length appears, due to the occurrence of intarmolecular charge transfer (ICT) in D-A structure [28,29]. These conjugated materials have been synthesized and characterized to enhance the electrochemical and optical properties for instance low HOMO-LUMO gap values, fast switching time, high optical contrast and high conductivity [19,30,31].…”
Section: 4-dioksytiofen) (Pedot) a Strong Interaction Between O Anmentioning
confidence: 99%
“…When BT is incorporated with electron donor units, the extension of the conjugated length appears, due to the occurrence of intarmolecular charge transfer (ICT) in D-A structure [28,29]. These conjugated materials have been synthesized and characterized to enhance the electrochemical and optical properties for instance low HOMO-LUMO gap values, fast switching time, high optical contrast and high conductivity [19,30,31].…”
Section: 4-dioksytiofen) (Pedot) a Strong Interaction Between O Anmentioning
confidence: 99%
“…Holder and co‐workers established an efficient procedure for the construction of a variety of star‐shaped molecules ( 118 – 120 ) in which a 1,3,5‐triethynyl benzene core was directly connected to highly branched peripheral heteroaromatic units . The key precursors ( 115 – 117 ) were derived from 4,7‐dibromobenzothiadiazole ( 108 ) by employing Suzuki and Stille cross‐coupling reactions, followed by bromination with NBS (Scheme ).…”
Section: Carbon−carbon Bond Formationmentioning
confidence: 99%
“…In this regard, C 3 -symmetrical 1,3,5-triphenylbenzene (26)w as convertedi nto the corresponding1 ,3,5tris(4-iodophenyl)benzene ( 7)b yu sing iodine in the presence of orthoperiodic acid( H 5 IO 6 ). Next, triiodod erivative 7 was subjected to SM cross-coupling with 4-fluorophenylboronic acid (27)u nder palladium catalysis to provide compound 29.…”
Section: Suzuki-miyaura Cross-coupling Reactionsmentioning
confidence: 99%
“…107,108 Hexylthiophene-and substituted fluorene-boronic acid pinacol esters 116 were successfully used in the reaction with dibromobenzothiadiazole (112) producing the corresponding 4,7-bis(aryl)-2,1,3-benzothiadiazoles 114 in high yields (Scheme 54). [109][110][111][112][113] …”
Section: A Suzuki Couplingsmentioning
confidence: 99%
“…Sometimes instead of an organic base, a mixture of potassium carbonate and triphenylphosphine was used 155. In contrast to Suzuki and Stille couplings, monoalkynyl derivatives 130 can be obtained from 4,7-dibromo-2,1,3-benzothiadiazole(112) in high yields employing practically the same conditions as those used for the synthesis of dialkynyl benzothiadiazoles, with a smaller amount of terminal alkyne (Scheme 63) 156,157. It was shown that four ethynyl groups can be inserted to benzothiadiazole molecule in one step giving so called "carbon-rich BTD series."…”
mentioning
confidence: 99%